PENGARUH DUKUNGAN SOSIAL, IKLIM ETIKA, DAN KOMITMEN ORGANISASI TERHADAP NIAT PINDAH (TURNOVER INTENTION) KARYAWAN PADA PT. BANK TABUNGAN NEGARA (BTN) PERSERO, TBK CABANG KENDARI - Farach Astari; Alida Palilati; Halim Halim (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2017)
This study aims to: (1). To find out and analyze the simultaneous influence of social support, ethical climate and organizational commitment to the turnover intention of PT. State Savings Bank (BTN) Persero, Tbk Branch Kendari, (2) To find out and analyze the influence of social support on turnover intention on employees of PT. State Savings Bank (Persero) Tbk, (3) To find out and analyze the influence of the ethical climate on turnover intention on employees of PT. State Savings Bank (Persero) Tbk. (4) To find out and analyze the effect of organizational commitment on turnover intention on employees of PT. State Savings Bank (Persero) Tbk.The population in this study were all employees of PT. State Savings Bank (BTN) Persero, Tbk Kendari Branch, amounting to 60 permanent employees, spread in the Main Branch Offices, Cash Offices and Sub-Branch Offices. Hypothesis testing is done by using multiple regression analysis.The results showed that: (1) social support, ethical climate and organizational commitment simultaneously had a significant effect in encouraging employees to intend to leave work from the company to find better employment opportunities than those available. (2) social support partially has a significant influence on employees' intention to leave the company where they work. (3) the ethical climate partially has a significant influence on the intention to leave company employees. (4) Organizational commitment partially has a significant influence in encouraging company employees to intend to leave work in the banking company.